2017
DOI: 10.15171/jcvtr.2017.11
|View full text |Cite
|
Sign up to set email alerts
|

The effect of statins on the organs: similar or contradictory?

Abstract: Hydroxy-Methyl-Glutaryl-CoA reductase (HMGCR) – the main enzyme of the cholesterol biosynthesis pathway – is mostly inhibited by statins in hepatocytes. In spite of the other tissues, liver utilizes cholesterol in different ways such as the synthesis of bile acids, excretion in to the intestine and synthesis of lipoproteins. Therefore, statins theoretically alter these pathways; although, there have not been such effects. In this review, we aim to show the roles of extra-hepatic tissues, in particular intestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…In addition to inhibition of HMG-CoAR, statins have demonstrated actions at the transcription level, with increases in nuclear receptor peroxisome proliferator-activated receptor alpha (PPARα), mediated by the Rho-signaling pathway, potentially explaining increases in high-density lipoprotein cholesterol (HDL-C) levels with statin therapy [ 32 ]. Statins also influence the expression of a wide range of other genes, including transcription factors involved in inflammation, proliferation, and differentiation [ 33 , 34 ], and cholesterol transporters in a range of tissues, including the liver, intestine, adipose tissue, and skin, and apolipoprotein A1 (apo-A1) in the liver ( Figure 2 ) [ 35 ]. This leads to an increased transfer of cholesterol to apo-A1, leading to a greater production of HDL.…”
Section: Effect Of Ryr On Ldl-c Plasma Level and Estimated Risk Of Ascvdmentioning
confidence: 99%
“…In addition to inhibition of HMG-CoAR, statins have demonstrated actions at the transcription level, with increases in nuclear receptor peroxisome proliferator-activated receptor alpha (PPARα), mediated by the Rho-signaling pathway, potentially explaining increases in high-density lipoprotein cholesterol (HDL-C) levels with statin therapy [ 32 ]. Statins also influence the expression of a wide range of other genes, including transcription factors involved in inflammation, proliferation, and differentiation [ 33 , 34 ], and cholesterol transporters in a range of tissues, including the liver, intestine, adipose tissue, and skin, and apolipoprotein A1 (apo-A1) in the liver ( Figure 2 ) [ 35 ]. This leads to an increased transfer of cholesterol to apo-A1, leading to a greater production of HDL.…”
Section: Effect Of Ryr On Ldl-c Plasma Level and Estimated Risk Of Ascvdmentioning
confidence: 99%
“…The fact that purified human anti-HMGCR antibodies are directed against some rat liver cells is not surprising because hepatocytes are responsible for the synthesis of 60-70% of the cholesterol for the whole body [9]. HMGCR is mainly expressed in periportal hepatocytes, as reflected by the HALIP.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been suggested that statins may prevent the formation and rupture of aneurysms[4], but this finding has been refuted by other studies which find no effect[5,6]. Interestingly, statins can have the effect of either increasing or decreasing macrophage-mediated cholesterol efflux, though with an overall preference for inhibiting this process[39]. This would lend theoretical mechanistic credibility to the potential utility of statins as a rupture-prevention therapy via the reduction of macrophage-associated cholesterol efflux (found to be associated with rupture in our results).…”
Section: Discussionmentioning
confidence: 99%